PERSEPSI MAHASISWA FISIOTERAPI TERHADAP PENGEMBANGAN MODUL MATA KULIAH FISIOLOGI MANUSIA DENGAN METODE PEMBELAJARAN PROBLEM BASED LEARNING - Yeni Vera (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2021)
This study was aimed to find the perceptions of physiotherapy students with the application of the Problem Based Learning method in lectures, especially courses in human physiology. This was descriptive analytical with survey method, the subject of this study is physiotherapy student who has received a physiology course and follows the learning process with the Problem Based Learning (PBL) method with 32 research subjects. The results of the study showed that the level perception of physiotherapy students in the STIKes siti hajar medan with PBL method was good (84%). Perception based on the category, 54% of respondents have perceptions in the favorable category while the percentage for each statement is 30 % unfavorable. there is an improvement in the value of students before applying the PBL method after applying the PBL method. As a result, the average score of students from score 68 becomes a score of 80. Changes in grades are better in the learning process, the level of understanding and knowledge of lectures especially human physiology becomes information important for students and lecturers